2006
DOI: 10.1080/13668250600876459
|View full text |Cite
|
Sign up to set email alerts
|

Rater bias and the measurement of support needs

Abstract: Our results suggest that support measures such as SNAP may significantly overestimate support needs when raters know the assessment is being used for funding purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…Ratings of support needs have been shown to be affected significantly by raters knowing whether the ratings are for the purpose of funding or research. 22 In the present study, Rater 1 knew that the rating would directly impact on how long the client concerned would wait for services, and may have been influenced by a number of factors (such as the strength of a verbal case made by either a client or referrer, or sympathy for a client's situation). Rater 2 was rating purely for the purpose of research, which may have allowed a more objective view.…”
Section: Discussionmentioning
confidence: 99%
“…Ratings of support needs have been shown to be affected significantly by raters knowing whether the ratings are for the purpose of funding or research. 22 In the present study, Rater 1 knew that the rating would directly impact on how long the client concerned would wait for services, and may have been influenced by a number of factors (such as the strength of a verbal case made by either a client or referrer, or sympathy for a client's situation). Rater 2 was rating purely for the purpose of research, which may have allowed a more objective view.…”
Section: Discussionmentioning
confidence: 99%
“…More recent instruments, such as the SIS , have assumed that support needs involve more than adaptive and challenging behaviour, although, as noted, some studies have reported very strong associations between support need assessments and adaptive behaviour (Guscia et al . ; Brown et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Guscia et al . ). Validation against funding level is further compromised by the major differences in funding across service types and funding programmes (Stancliffe & Lakin , ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, an investigation into rater bias in the SNAP found inflated scores when raters were aware of the fact that the assessment results were to be used for funding purposes as opposed to research purposes. Guscia et al. (2006a) concluded that such measures may seriously overestimate support needs when raters know that the assessment is being used for funding purposes.…”
Section: Introductionmentioning
confidence: 99%